Mechanical Properties of Sandwich Composite using Glass Fiber Reinforced Polymer as A Skin and 3D Printed Polylactic Acid as A Core - Muhammad Ridlwan; Faisal Arif Nurgesang; Rahmat Riza; Nur Muhammad Syafi'i (Journal of Mechanical Engineering, Science, and Innovation, 2022)
Recently, 3D printing technology has become a practical method to realize products rapidly. It is suitable for making small quantities of products. Although it is capable of printing with a high level of geometric complexity, there is a lack of tensile strength due to its process where the products are printed layer by layer. However, this technology is potentially to be combined in a composite manufacturing process. Mostly, a composite product is made by using a mold. This mold is relatively expensive and can only create a product with less complexity. Nevertheless, the composite product has main advantages such as light, strong, and flexible. Therefore, combining these two technologies is a new breakthrough in realizing products with high complexity, light, strong, and flexible. This study aims to determine the mechanical properties of sandwich composite filled with 3D printed product as a core. Several parameters were varied including core thickness and skin thickness. The skin material was a Glass Fiber Reinforced Polymer (GFRP) while the core material was 3D printed Polylactic Acid (PLA). The tensile and bending tests have been done in accordance with ASTM D638 and ASTM D790. The results showed that the addition of GFRP skin on the sandwich composite could significantly increase the tensile strength but did not have an impact on the flexural strength. The highest flexural strength of 50.36 MPa was achieved at 3 layers of GFRP skin while a remarkable tensile strength of 55.74 MPa was obtained at 4 layers GFRP skin. Moreover, the addition of core thickness also does not have an impact on flexural strength. The flexural strength of the 3D printed core was around 20 MPa for all thickness. However, when 2 layers of GFRP skin were used, a remarkable flexural strength of 57.67 MPa was obtained but the flexural strength was then decreased when using 10 and 15 mm cores.